A comparative investigation of therapeutic effects of rose and lavender aromatherapy on hemodynamic symptoms of recently diagnosed diabetic patients: A single-blind randomized cross-over controlled clinical trial - Pooneh Yousefi; Saeed Hosseini Teshnizi; Aref Faghih; Mohammad Hossein Taklif (Journal of Research in Clinical Medicine)
Introduction: Diabetes is a chronic and widespread problem with broad effects on human physiological systems, including significant impacts on hemodynamic symptoms, which can significantly affect the patient’s recovery process and quality of life. This study was conducted to compare the effects of rose and lavender aromatherapy on hemodynamic symptoms in patients with a recent diabetes diagnosis. Methods: In this cross-over controlled clinical trial study, three distinct groups were employed: two experimental groups (aromatherapy with rose and lavender) and a single control group. Pre-test and post-test assessments were conducted before and after the intervention on a total of 45 diabetic patients in 2022 at the Hormoz Clinic in Bandar Abbas. The interventions occurred over three sessions, with each patient receiving different treatments during different periods (first, second, and third stages). A one-week washout period was implemented between the stages to mitigate any potential carryover effects. Before initiating the interventions, demographic variable questionnaires and hemodynamic symptoms (systolic and diastolic blood pressure, and pulse rate) were documented both before and after the interventions. Data were analyzed using Stata version 14.0 and SPSS version 26 statistical software. Results: The mean diastolic blood pressure (P=0.459), systolic blood pressure (P=0.908), and pulse rate (P=0.125) did not differ significantly between the three groups before the intervention. However, there were significant differences in mean diastolic blood pressure (P<0.001) and mean pulse rate (P<0.001) in the post-intervention of the three groups. Conclusion: Aromatherapy treatments using rose and lavender essential oils can contribute to the stabilization of some Hemodynamic Symptoms.